Palliative Care in Myocardial Infarction: Patient Characteristics and Trends of Service Utilization in a National Inpatient Sample. (August 2019) - Abdullah, Abdullah Sayied; Salama, Amr; Ibrahim, Hisham; Eigbire, George; Hoefen, Ryan; Alweis, Richard
Introduction: Myocardial infarction (MI) remains a leading cause of mortality. Palliative care (PC) has recently expanded in scope to include noncancer-related conditions. There is little data available regarding the use of PC in critical MI patients. Methods: We used discharge data from the National Inpatient Sample for the years 2012 to 2014. We examined discharges with a primary diagnosis of MI. We measured the rate of PC referral, trend in utilization during the study period and possible predictors of PC utilization. Results: Among 1 667 520 discharges of those patients ≥18 years of age and with a primary diagnosis of MI, use of PC was seen in 2.5% of all patients and in 24% of patients who died. In a multivariable logistic regression, we found the presence of cancer, cardiogenic shock, dementia, stroke, hemiplegia, the use of circulatory support, and mechanical ventilation were associated with higher likelihood of PC referral. Palliative care referral increased during the study period, odds ratio of 1.18 per year (95% confidence interval: 1.14-1.21; P value <.001). Palliative care was not associated with prolonged length of stay. Conclusion: Several comorbidities were associated with the use of PC, most notably the use of mechanical ventilation and the presence of metastatic cancer. There was a trend of increasing use of PC during the study period.